Fundraising Strategies in Improving Student Organizations At Al-Maun Shelter in Bengkulu City - Fadlurrohim, Ishak; Rosi L Vini Siregar; Yessilia Osira (Universitas Dinamika, 2025)
Community service activities are carried out by providing knowledge and skills about fundraising strategies in improving student organizations at the al-maun shelter in Bengkulu City. Fundraising strategy is one of the efforts that can be made to obtain funding sources in carrying out activities and activity programs, through this fundraising strategy can reduce dependence on major donor institutions. The method applied during the service activity is qualitative descriptive using the case study menggunakan tools the PRA (Participatory Rural Appraisal) and Focus Group Discussion approach by determining purposive sampling informants with the criteria of 40 volunteers who are active at the Al-Maun Shelter House in Bengkulu City, improve and analyze knowledge about fundraising strategies. data collection through FGD, in-depth interviews, and field surveys. There are 2 strategies that have been implemented but need to be improved, namely, first, the Donor Retention and Development Strategy, fund collecting units and bookkeeping are needed for transparency to donors and the involvement of community leaders. Second, Multichannel Fundraising Strategy is needed to expand information networks and the role of community leaders can play an important role in providing understanding to the community. Corporate Fundraising dan Strategi Dialogue Fundraising have limitations in the implementation of activities that depend on other institutions/organizations. So, a written agreement is needed.